A study of health conditions of nursing student Boromarajonani College of Nursing Sunpasitthiprasong During 2018-2021 C.E. - Promkaew, Orathai; Bonlom, Teeraporn (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2024)
This research is a retrospective descriptive study aimed at examining changes in the health status of Bachelor of Nursing students from Boromarajonani College of Nursing Sunpasitthiprasong across two cohorts (the 48th with 175 students and the 49th with 196 students). The study analyzed annual health examination results from 2018 to 2021, covering the 2nd, 3rd, and 4th years of study. The health examinations included measurements of body mass index (BMI), vital signs and blood pressure, completed blood count or packed red blood cell volume (HCT), and chest radiographs. Each examination result was evaluated to classify as normal or abnormal. The data were then analyzed using frequency distribution, percentage, and average. The results showed that the majority of the students’ health conditions were within normal levels, with only small portion exhibiting abnormalities. Significant changes in BMI were observed during the 3rd and 4th years of study. The percentage and average results were as follows: 1) body mass index (BMI): Both cohorts had dangerously high obese levels, with averages of 4.54% for the48th generation and 1.02% for the 49th generation. The total BMI exceeded the criteria, with the 48th generation having a higher average percentage than the 49th generation (25.68% vs.17.34%). 2) high blood pressure: Abnormal high blood pressure (level 1) was observed in 0.57% of the 48th generation and 0.51% of the 49th generation. 3) Complete blood count (HCT): The packed red blood cell volume was lower than normal in 9.14% of the 48thgeneration and 11.73% of the 49th generation. 4) Chest X-ray: Abnormal thoracic bone characteristics were found in 2.29% of the 48th generation and 1.53% of the 49th generation. To address health issues, several key recommendations should be considered. Firstly, any abnormal findings from health assessments should be followed up with diagnostic tests and treatment to ensure appropriate care. Secondly, activities should be organized to inform students about periods when health conditions and BMI may change, and to provide strategies for prevention. Finally, encouraging 3rd and 4th-year students to participate in outdoor activities is crucial. Promoting physical exercise helps reduce factors contributing to increased BMI and supports overall well-being.